Draft genome sequence and crude violacein production of biowaste-grown Chromobacterium violaceum Strain RS2B1 isolated from Nag-aso Boiling Lake, Albay, the Philippines - Balla, Charlene B. (Philippine Journal of Science, 2025)
Violacein is a violet pigment produced by Chromobacterium violaceum known to have antioxidant, antileukemic, and antimicrobial activities, among others. A thermotolerant isolate (RS2B1) was further characterized for preliminary optimization of violacein production. The draft genome of RS2B1 was assembled from the paired-end Illumina NovaSeq sequence reads using the Proksee pipeline, producing a 4.75Mb genome composed of 69 contiguous sequences (L50 = 5, N50 = 0.39Mb) that passed NCBI exclusion criteria. The average nucleotide identity, digital DNA-DNA hybridization, and annotation with Prokka and RAST supported RS2B1’s taxonomic assignment and comparable gene content, whereas antiSMASH also showed the violacein gene cluster found in other strains. The crude violacein of RS2B1 was also verified to exhibit antibacterial activity against Gram-positive microorganisms. Additionally, this study showed that RS2B1 can be grown in acid-hydrolyzed cellulosic waste (CW) and autoclaved fish waste (FW), as it is metabolically adaptable. A significant two-fold increase in crude violacein yield was observed in set-ups grown With CW and Low FW (WCLF) or at No CW and High FW (NCHF) compared to commercial media. This study also screened conditions affecting violacein production in RS2B1 and the highest yield was obtained at 35 °C than at 44 °C (600–1,100 µg/L, p < 0.001), static than at 50 rpm shaking (100–400 µg/L, p < 0.01), either at 48 (WCLF = 1,828 µg/L) or 96 (NCHF = 1,360 µg/L) hours of incubation (p < 0.001). An attempt to optimize media formulation using the Box-Behnken design showed that the highest yield can be produced at 0% CW, 30% FW, and 53.17 h of incubation, potentially yielding 787.19 µg/L crude violacein. In conclusion, this study was the first to demonstrate FW as an alternative substrate in producing violacein in the RS2B1 isolate, but further study on its optimization is recommended.